Physiological and Proteomic Analyses of Molybdenum- and Ethylene-Responsive Mechanisms in Rubber Latex - Gao, Le; Sun, Yong; Wu, Min; Wang, Dan; Wei, Jiashao; Wu, Bingsun; Wang, Guihua; Wu, Wenguan; Jin, Xiang; Wang, Xuchu; He, Peng (Frontiers in Plant Science, 2018)
Molybdenum (Mo) is an essential micronutrient in many plants. In the rubber tree Hevea brasiliensis, Mo application can reduce the shrinkage of the tapping line, decrease tapping panel dryness, and finally increase rubber latex yield. After combined Mo with ethylene, these effects become more obvious. However, the molecular mechanism remains unclear. Here, we compared the changed patterns of physiological parameters and protein accumulation in rubber latex after treated with Mo and/or ethylene (Eth). Our results demonstrated that both Eth and Mo can improve the contents of thiol, sucrose and dry yield in rubber latex. However, lutoid bursting is significantly inhibited by Mo. Comparative proteomics identified 169 differentially expressed proteins, including 114 unique proteins, which are mainly involved in posttranslational modification, carbohydrate metabolism and energy production. The abundances of several proteins involved in rubber particle aggregation are decreased upon Mo stimulation, while many enzymes related to natural rubber biosynthesis are increased. Comparison of the accumulation patterns of 25 proteins revealed that a large portion of proteins have different changed patterns with their gene expression levels. Activity assays of six enzymes revealed that Mo stimulation can increase latex yield by improving the activity of some Mo-responsive enzymes. These results not only deepen our understanding of the rubber latex proteome but also provide new insights into the molecular mechanism of Mo-stimulated rubber latex yield.